Dualism of Islamic Education Identities in Indonesia: Schools and Madrasah - Ahmad, Heryan Fandi; Anggraini, Reni Dwi; Susilowati, Samsul; Sadewa, Garin; Hady, M. Samsul; Asrori, Muhammad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
This article discusses the dynamics of dualism in Islamic education in Indonesia, which lasted from the colonial period to the modern era. This dualism is reflected in the separation between public schools and madrasahs, each of which has different curriculum characteristics, management, and educational goals. Public schools tend to focus on mastering science and technology, while madrasahs emphasize in-depth religious education, although both have the same national goal of educating the nation's life and shaping the character of students. Through a desk research approach and historical analysis, this article reviews the historical roots of dualism, government policies, and curriculum comparisons between the two institutions. It is found that this difference causes challenges in the integration of the education system, especially regarding management, quality of resources, and public perceptions. However, through the implementation of the Merdeka Curriculum, particularly through P5 and P5RA, there are efforts to unify religious and national values in the education system. This article recommends the importance of synergy between schools and madrasahs in order to achieve inclusive and sustainable national education quality.